Review of two types of surface modification on pool boiling enhancement: Passive and active. (September 2020) - Li, Wei; Dai, Renkun; Zeng, Min; Wang, Qiuwang
Abstract: Many methods for enhancing nucleate pool boiling have been proposed to improve the two-phase heat transfer performance in recent years. This article offers a comprehensive comment from published literature in terms of the surface modification of reinforcing heat transfer. Two types of surface modification regarding enhancement of boiling heat transfer coefficient and critical heat flux are categorized for the first time in this paper. The first and most widespread way is artificially changing the characteristics of the surface in advance to improve boiling performance, such as structured surface and surface coating with nanoparticles, namely, the "passive" technology. Oppositely, the "active" one on boiling enhancement seems to have more potential for development and it is favored by some researchers. In brief, the transformation of geometrical shape or characteristics such as wettability spontaneously occurs during boiling, the critical heat flux would thus be delayed. The heat transfer performance, as a result, would be significantly ameliorated. This kind of "smart surface" is usually made up of specific shape memory alloy, polymers, metallic oxides, etc. The mechanisms of boiling enhancement regarding modified surfaces are also reviewed, the capillary wicking, for instance, plays vital role in it. Moreover, various surfaces are presented with emphasis on their advantages/disadvantages. Through the analysis and comparison of the two kinds of modified surfaces, this review also points out some challenges existing in the current studies concerning this topic, such as numerical study, which are worth solving or optimizing to efficiently and economically improve the boiling heat transfer in future. Highlights: Pool boiling enhancement by the modified passive and active surface are reviewed. The critical factors for boiling enhancement and mechanisms are analyzed. Smart surfaces have promising applications although related study is rare. Opportunity and challenge coexist for pool boiling enhancement techniques.